Performance of Blackgram and their Improved Variety in Chhatarpur Districts under Bundelkhand Region of Madhya Pradesh - Tripathi, U.K.; Singh, R.K.; Srivastav, Veenapani (Indian Journal of Extension Education, 2019)
Consistent efforts to popularize the improved variety PU 35 of blackgram along with recommended production since kharif 2011 are being taken up in District Chhatarpur by KVK for enhancing the yield and income of farmers. Since most of the farmers lack knowledge and adoption of high yielding diseases resistant varieties and thereby harnessing lower yields culminating in limited net returns. The performance of blackgram production through varietal replacement under central portion on the plateau of Bundelkhand region in Madhya Pradesh, showed that by the end of 2018, 65.1 and 16.8 per cent area has been occupied with blackgram and their improved variety ‘PU 35 with an increase in yield by 489 kg per ha and net returns by 46.5 per cent over locally cultivated varieties. Maximum yield (10.29 q/ha) was obtained during 2018-19. During 2013-14 and 2015 (rainfall 1300 and 1161.4 mm) the improved variety of blackgram (PU 35) produced lower yields (907 & 925 q/ha) which showed that this variety can also perform better under average rainfall regime. The returns per rupee investment varied between 2.7 to 2.9 whereas it was 1.3 to 1.4 in locally cultivated varieties with traditional farmers practice during 2011 to 2018.
Keywords: Economic impact; Improved varieties; Impact and Spread of technology